Psidium guajava fruit peel extract reduces oxidative stress of pancreas in streptozotocin-induced diabetic rats - Siti Balkis Budin,; Hawa Ismail,; Pek, Lian Chong (Universiti Kebangsaan Malaysia, 2013)
Abundant natural products with medicinal properties have been used as food and traditional medicine for diabetes mellitus all over the world. Psidium guajava fruit from the family of Myrtaceae has gained attention for its antioxidant potential. This study was conducted to determine the effects of P. guajava fruit peel aqueous extract on oxidative stress of pancreas in streptozotocin-induced (45 mg/kg) diabetic rats. Diabetic rats were administered with 400 mg/kg of aqueous extract of P. guajava fruit peel daily for 28 days duration. The results showed that diabetic rats supplemented with P. guajava extract did not cause significant difference in blood glucose level (p>0.05) as compared with diabetic rats alone. For oxidative stress evaluation, malondialdehyde (MDA) and protein carbonyl level were significantly lower and the activity of superoxide dismutase (SOD) and glutathione (GSH) level were significantly higher (p<0.05) in P. guajava supplemented rats compared with non-supplemented diabetic rats. However, histological observation showed that supplementation of P. guajava extract did not give protective effects towards alterations in pancreas histology in diabetic rats. The findings suggested that aqueous extract of P. guajava fruit peel supplementation has the ability to reduce oxidative stress in pancreas of diabetic rats and may play a role in reducing the development of diabetic complications.